2004
DOI: 10.1002/cncr.20370
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survivorship in a multiethnic sample

Abstract: BACKGROUNDThe inclusion of ethnic minorities in cancer‐related studies continues to be an important concern for researchers. In this article, the authors present 1) a brief discussion of recruitment and measurement challenges in conducting multiethnic survivorship research, and 2) recruitment outcomes and sample characteristics for a health‐related quality‐of‐life study with a multiethnic sample of breast cancer survivors (BCS).METHODSA case–control, cross‐sectional design with mixed sampling methods was used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 35 publications
2
59
1
Order By: Relevance
“…Due to the cascade of issues related to breast cancer survivorship, as well as the growing population of breast cancer survivors, such studies have become a top priority [9,18]. It is critical to note that the physical and mental health outcomes of long-term breast cancer survivorship are mediated by social support [20], ethnicity [21], living situation and partnership status [8], sexuality issues [22], socioeconomic status [23], and fatigue level [24]. Thus, breast cancer survivorship is differentially experienced across sociodemographic and clinical factors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the cascade of issues related to breast cancer survivorship, as well as the growing population of breast cancer survivors, such studies have become a top priority [9,18]. It is critical to note that the physical and mental health outcomes of long-term breast cancer survivorship are mediated by social support [20], ethnicity [21], living situation and partnership status [8], sexuality issues [22], socioeconomic status [23], and fatigue level [24]. Thus, breast cancer survivorship is differentially experienced across sociodemographic and clinical factors.…”
Section: Introductionmentioning
confidence: 99%
“…The internal consistencies of the scales by language (English, Spanish, Chinese, and Korean) and ethnicity (Latina and Asian) were assessed by using Cronbach's alpha, and no differences based on language and ethnicity were found. Reliability and validity tests indicated that the standard and new measures used are appropriate for assessing HRQOL with this diverse BCS sample (Cronbach's alpha=0.66-0.92) [29]. Table 1 presents the measures of variables.…”
Section: Methodsmentioning
confidence: 99%
“…All procedures for the study reported here were approved by the University of California, Los Angeles Institutional Review Board. Details regarding subject identification and recruitment are described elsewhere [29].…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The methodology including sampling procedures, instrumentations, and data managements for this study has been addressed in detail elsewhere (Ashing-Giwa et al 2004b). A brief overview of the methods, procedures, and instrumentation follows.…”
Section: Methodsmentioning
confidence: 99%